Analisis Film Ipar Adalah Maut Oleh Elizasifaa Menggunakan Pendekatan Mimetik - Zachra, Nayshilla (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to describe literary criticism using a mimetic approach in the film "Ipar is Death" published by Elizasifaa through someone's true story. The research method used in this analysis is a qualitative descriptive approach which focuses on in-depth understanding of social phenomena in the form of descriptive data with observational data collection techniques, namely listening and note-taking techniques in examining the film evidence using a mimetic approach. The film "In-law is death" published by Elizasifaa, directed by Hanung Bramantyo, has lessons for every couple about the importance of maintaining boundaries in family relationships, especially between siblings of the opposite sex who are not their mahram. There are nine dialogue quotes in the film that support the perception of mimetics by using references. from other sources, namely news and podcasts.